Measuring halal cosmetics consumers among Indonesian women - Suci Wulandari; Fetria Eka Yudiana (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2022)
This study aims to determine the effect of Halal Certification, Celebrity Endorser, and Price on Purchase Decisions of Halal Cosmetic Products through Brand Image as an Intervening Variable case study on Maybelline consumers in Salatiga City. The object of this research is consumers of Maybelline cosmetic products in Salatiga City, with a sample of 100 people using a convenience sampling technique. The analysis method in this study uses path analysis. The results of the T-test show that the Halal Certification and Celebrity Endorser variables do not affect Brand Image. In contrast, the Price variable positively and significantly affects Brand Image. Halal certification has a negative and significant effect on Purchase Decisions, and Celebrity endorsers and price have a positive and significant effect on Purchase Decisions. Path Analysis test results show that Brand Image cannot mediate the effect of Halal Certification and Celebrity Endorser on Purchase Decisions. In contrast, Brand Image can mediate the effect of Price on Purchase Decisions.